NUTRITIONAL INTERVENTIONS AND COGNITIVE OUTCOMES IN CHILDREN FROM TWO TO SIX YEARS OF LIFE - Stepanović, Ivana; Radovanović, Jovana (HEALTH CARE, 2026)
The development of cognitive abilities in children aged 2 to 6 years is significantly influenced by nutritional status. This research examines the effectiveness of nutritional interventions that depend on biological, social, and educational factors. Prenatal supplementation and higher maternal education are associated with more favorable cognitive outcomes, while children born with low birth weight show longer-lasting delays. The effectiveness of interventions varies. Multinutrient supplementation with five or more nutrients demonstrates a broader impact on cognitive functions compared to targeted supplementation. The period between 6 and 18 months of age is particularly important for the implementation of intervention programs. Integrating nutritional support with educational approaches that include structured play and physical activity can promote the parallel development of motor and cognitive skills. Methodological challenges include the need for randomized controlled trials, longer follow-up periods, and the use of laboratory biomarkers to assess nutrient status. Results indicate that the effects of interventions depend on the initial nutritional and health status of the child, the duration of treatment, and the social context. Recommendations for future work include expanding research to rural populations and children with special needs, standardizing measurement methods, and conducting long-term monitoring to assess the sustainability of benefits. This holistic approach emphasizes the importance of coordination between the health and education sectors to enhance cognitive development.
Keywords: cognition, preschool age, nutrition